Pemanfaantan Bubuk Arang Kayu Terhadap Stabilitas Tanah Lempung di Dusun Jatiluhur, Banyuwangi - Melati Nurita Sandi, Dora; Wendy Natasha, Levia; Ulfiyati, Yuni; Suryani, Erna (Indonesian Society of Applied Science, 2022)
The type of soil in Glagah Agung Village, Purwoharjo District, Banyuwangi Regency, is a type of clay soil with a plasticity index value of 42.99. Based on Expansive Land Management for Road Construction by Departemen Pekerjaan Umum Pd T-10-2005-B, it is classified as soil with a high swelling level. So that it can be categorized into soils with high Swelling and shrinkage. The soil improvement method using wood charcoal powder stabilizer was chosen because it can improve water and air circulation in the soil. This study used the addition of wood charcoal powder percentage of 0%, 6%, 8%, 10%, 12%, 14%. The research was conducted on the original soil and stabilized soil specimens, to test their physical properties. The soil physical properties test included water content, specific gravity, atterberg limit, proctor, submerged and unsubmerged CBR. Based on the results of the non-submerged CBR test, the CBR value increased along with the addition of the percentage of wood charcoal powder as a stabilizer. Where the highest CBR value is at the percentage of 14% stabilizers, which is 16.956%. Based on the results of the submerged CBR test, the CBR value decreased at 10% satbilisator percentage and then increased to 14% satbilisator percentage. The highest swelling rate occurred in soil stabilized with 10% wood charcoal powder, which was 0.306.